Thermal A-δ Nociceptors, Identified by Transcriptomics, Express Higher Levels of Anesthesia-Sensitive Receptors Than Thermal C-Fibers and Are More Suppressible by Low-Dose Isoflurane. (July 2018) - Raithel, Stephen J.; Sapio, Matthew R.; Iadarola, Michael J.; Mannes, Andrew J.
Abstract : We investigated the effect of isoflurane on 2 main types of thermal nociceptors: A-δ and C-fibers. Surprisingly, 1% inhaled isoflurane led to a hyperalgesic response to C-fiber thermal stimulation, whereas responses to A-δ thermal stimulation were blunted. We explored the hypothesis that differences in withdrawal behavior are mediated by differential expression of isoflurane-sensitive proteins between these types of thermal nociceptors. Multiple transcriptomic databases of peripheral neurons were integrated to reveal that isoflurane-susceptible proteins Htr3a, Kcna2, and Scn8a were enriched in thermosensitive A-δ neurons. This exploratory analysis highlights the differing role that volatile anesthetics might have on nociceptors in the peripheral nervous system.